Enhancement of Spontaneous Parametric Down-Conversion in Nonlinear Metasurfaces - Fedotova, Anna; Santiago-Cruz, Tomas; Sultanov, Vitaliy; Weissflog, Maximilian; Younesi, Mohammadreza; Staude, Isabelle; Pertsch, Thomas; Setzpfandt, Frank; Chekhova, Maria V. (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
We experimentally demonstrate biphoton generation by spontaneous parametric down-conversion in resonant metasurfaces. In our metasurfaces, Mie-type resonances enable over 7 times more efficient biphoton generation compared to an unstructured thin film.
CRIS-Team Scopus Importer:2021-12-24